Поглинання та релаксація енергії лазерного випромінювання в речовині (огляд) - Semchuk, O. Yu.; Havryliuk, O. O. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
Each stage of interaction of laser radiation with the surface of the absorbing medium is considered in detail. First, processes occurring inside the electron and phonon subsystems are considered, then pulsed laser excitation and relaxation of the electronic subsystem. It is believed that intraband energy relaxation in the electron subsystem in the high-excitation regime occurs over a time on the order of the electron-electron relaxation time τе-е. Due to this, the entire energy of the laser pulse absorbed in a time of the order of τе-е remains inside the plasma subsystem of the semiconductor and is thermalized. The energy distribution of electrons and holes remains thermal and is characterized by identical electron (Te) and hole (Th) temperatures. Wherein Te=Th=Tc. The latter value of Tc depends on the concentration of nc and at nc = 1021 cm-3 can reach values of the order of 104 K.